Analisis Tingkat Kepuasan Konsumen terhadap Kualitas Produk dan Pelayanan di “Waroeng Kampoeng” Jimbaran menggunakan Metode Customer Satisfaction Index (CSI) dan Potential Gain Customer Value (PGCV) - Wisanggeni, Pandu Desta; Hartiati, Amna; Sadyasmara, Cokorda Anom Bayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 4 (2020): Desember, 2020)
"Waroeng Kampoeng" is a culinary business that has a menu variant of Chinese food & Indonesian food which is always crowded with visitors, however, an analysis of customer satisfaction is needed to support the successful achievement of satisfaction from service and product quality at a restaurant. The purpose of this research is to (1) find out what attributes are considered important by consumers for achieving customer satisfaction with the quality of products and services in "Waroeng Kampoeng" (2) to measure the performance of services provided "Waroeng Kampoeng" for customer satisfaction (3) determine the level customer satisfaction with products and services in "Waroeng Kampoeng" (4) determine the attributes that need to get priority from the company based on the level of importance and performance to provide satisfaction with customer satisfaction in "Waroeng Kampoeng". The method used to measure the level of customer satisfaction in this study is by distributing questionnaires to 95 selected respondents and will be calculated using the Customer Satisfaction Index (CSI) and Customer Benefit Potential Value (PGCV) with two observed service quality variables, namely direct evidence. , reliability, responsiveness, assurance and empath. Meanwhile, the second variable is the product quality variable which is observed is menu, price, and promotion. The results showed that there are 2 important attributes in determining customer satisfaction with service quality at "waroeng Kampoeng", namely direct evidence and assurance. Meanwhile, the product quality in "Waroeng Kampoeng" is the price and product. The service performance that is already good at "waroeng Kampoeng" is direct evidence that includes cleanliness of the place, cleanliness of the equipment used and WIFI facilities, while what includes guarantees is employee knowledge of the menu, transaction convenience and employee behavior. While the product performance that is already good in "waroeng Kampoeng" is the quality of the product which includes the taste of the drink, the presentation of the drink, the suitability of the food price with the portion, the suitability of the price of the drink with the portion, the variety of the food menu with quality, the suitability of the drink price with the quality and the suitability of the food price. with quality. Based on the customer satisfaction index service quality in "waroeng kampoeng" obtained 79% and the product quality customer satisfaction index in "waroeng kampoeng" 78%, which is included in the satisfied category. The PGCV results show that the attribute that needs to be improved from service quality is employee behavior because the value obtained is 3.23 and the attribute that needs to be improved from the product quality is the suitability of the price of the drink  with the quality with the value obtained of 2.93 . Keywords : customer satisfaction index, quality of product, quality of service, potential gain customer value.